Ideology and the Simulacrum Concept of the Reality Interpretation in Dušan Kovačević’s Play “Balkanski špijun” - Marinkov, Jelena I. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
In this paper we tried to illustrate how various literary and philosophical theories can be applied to interpretation of the play “Balkanski špijun” (“Balkan Spy”) by a famous contemporary Serbian playwright, Dušan Kovačević. In the introductory part of the paper, we analyzed the play “Balkanski špijun” according to the basic principle of Manfred Pfister’s drama theory—the overlapping of the internal and external communication system. We used Pfister’s theory to better explain in which ways reality figures in Kovačević’s play and to show that his work relies on comedies written by the great Serbian comedy writer, Kovačević’s predecessor, Jovan Sterija Popović. In the second segment of the paper, we considered the functioning of ideologically determined subjects, Ilija and Danica, and in the third and the central part of the work, we tried to present Ilija’s world as simulacrum induced. In all the segments of this work, we tried to show how modern theories related to different domains of human thinking can be successfully applied in the interpretation of a complex work of art such as “Balkanski špijun” by Dušan Kovačević.